Umowy o stowarzyszeniu z UE w ramach partnerstwa wschodniego – wybrane zagadnienia - Michalewski, Tomasz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The ENP is pursuing a policy of development cooperation carried out in accordance with the purposes and principles of the UE’s external action inaugurated in 2009. EaP assumes cooperation in the implementation of the ENP through economic cooperation and security and movement of persons between Eastern Europe and the Caucasus republics. Framework of cooperation with the EU are defined in the bilateral agreements concluded with each country separately, including activities related to political dialogue, trade reform, justice and home affairs. EU aid is primarily intended to promote enhanced cooperation and progressive economic integration between the European Union and its partners. Association Agreements are in the process of ratification in national parliaments partner countries and the Member States. Building democracy among the partners is the responsibility of citizens and their democratically elected governments. The ENP can support this process, but certainly not as a replacement.
Keywords: Europejska Polityka Sąsiedztwa; umowy; stowarzyszenia; Partnerstwo Wschodnie; Kaukaz Południowy; Europa Wschodnia